2010
DOI: 10.1007/s11706-010-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of crystallographic textures in chemical vapor-deposited diamond films

Abstract: Diamond is one of the most important functional materials for film applications due to its extreme physical and mechanical properties, many of which depend on the crystallographic texture. The influence of various deposition parameters matters to the texture formation and evolution during chemical vapor deposition (CVD) of diamond films. In this overview, the texture evolutions are presented in terms of both simulations and experimental observations. The crystallographic textures in diamond are simulated based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…As a result, grains with (110) orientation are longer (wider) in the film thickness (cross-plane) direction than grains with (111) orientation. Similarly, it has been reported that the (110) grain orientation is a preferred grain orientation for CVD diamond growth under certain conditions. As discussed above, these long (wide) grains scatter phonons less extensively in the cross-plane direction, resulting in longer phonon mean-free path and correspondingly higher thermal conductivity.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…As a result, grains with (110) orientation are longer (wider) in the film thickness (cross-plane) direction than grains with (111) orientation. Similarly, it has been reported that the (110) grain orientation is a preferred grain orientation for CVD diamond growth under certain conditions. As discussed above, these long (wide) grains scatter phonons less extensively in the cross-plane direction, resulting in longer phonon mean-free path and correspondingly higher thermal conductivity.…”
Section: Resultsmentioning
confidence: 68%
“…Similarly, it has been reported that the (110) grain orientation is a preferred grain orientation for CVD diamond growth under certain conditions. [62][63][64] As discussed above, long grains scatter phonons less extensively in the cross-plane direction, resulting in longer phonon mean free path and correspondingly higher thermal conductivity. To assess the cross-plane preferred grain orientation, Samples A1, B1, and ref1 were measured using XRD 2: scans.…”
Section: Enhanced Thermal Conduction In Diamond Membranesmentioning
confidence: 95%
“…The size of the diamond grains is typically a few nm close to the substrate and increases with the thickness of the film. The evolution of the grain size has been studied computationally [171,172] and experimentally [173]; it has been shown that, depending on the growth conditions, the lateral size of the grains and their aspect ratio are strongly changing with the film thickness. As a consequence, the grain boundary density varies with the depth of the PCD layer, translating into an inhomogeneous κ in-plane .…”
Section: Optimizing Diamond Cvd For Thermal Management Applicationsmentioning
confidence: 99%
“…In general, the deposited CVD films consisted primarily of (111) and (100) facets, depending on the growth velocity ratio of the <100> and <111> directions. It has been previously posited that substrate temperatures higher than 1170 K benefited the growth in the <100> direction while substrate temperatures lower than or equal to 1070 K benefited the growth in the <111> direction [8]. Experimental results of HCDC-PCVD were in keeping with that conclusion, considering the substrate temperature of 800 °C (1073 K) and the faceted grains which were dominated by the (111) texture as shown in Besides, there were ridges and steps oriented parallel to one other, manifesting twinning bands within the grains intersecting with the surface.…”
Section: Resultsmentioning
confidence: 99%